Reduction of chickens use to perform in vitro pre-screening of novel anticoccidials by miniaturisation and increased throughput of the current Eimeria tenella compound-screening model [version 2; peer review: 2 approved, 1 not approved] - Virginia Marugan-Hernandez; Javier Regidor-Cerrillo; Luis Ortega-Mora; Sara Arias-Maroto; Kelsilandia Aguiar-Martins (F1000Research)
We have developed an in vitro model for the evaluation of potential anticoccidial properties of novel compounds aimed to control chicken coccidiosis, a costly disease for the poultry industry. This disease is caused by protozoan parasites of the genus Eimeria (Apicomplexa), and it is mainly controlled by chemoprophylaxis with ionophores and chemical anticoccidials; however, there is an overall agreement about the limitation of these traditional drugs and the need to improve current methods of control. Anticoccidial activities of novel compounds is currently evaluated by expensive experiments that involve large numbers of chickens. The use of our in vitro model for the pre-screening of essential oils led to a reduction of 67% of the chickens used in the in vivo trials for validation. Eimeria parasites can only complete their life cycle in their animal host, therefore chickens are required for their propagation as they cannot be propagated in vitro. In this study, we describe how further optimisation of this in vitro model by miniaturisation can have an additional impact in reduction of the number of chickens used for the generation of parasite stocks for provision of the in vitro model. We have estimated that the use of one chicken could support the evaluation of 10 compounds with a 96-well plate format versus only two compounds with a 24-well plate format, which means an 80% reduction in chicken use. In this study we have proved that the miniaturisation into a 96-well plate format perfectly mimics the invasion and replication observed before in the 24-well plate format. In addition, the 96-well plate format has allowed the simultaneous pre-screening of higher numbers of anticoccidial drugs at different concentrations following streamlined protocols in a more cost-effective way, factors that are beneficial for a wider uptake of the model by other researchers investigating anticoccidial compounds.